Stakeholder-based decision support model for selection of alternative water sources - A path towards sustainable industrial future in Vietnam. (20th January 2023) - Bhatta, Astha; Le, Truong Minh; Wetser, Koen; Kujawa-Roeleveld, Katarzyna; Rijnaarts, Huub H.M.
Abstract: The combined effect of climate change, rapid industrialisation and traditional water use has created freshwater stress situations in industrial delta regions. Alternative Water Sources (AWSs) offer opportunities to mitigate the freshwater stress issue and, thus, contribute to a sustainable industrial future. This study developed a Decision Support Model (DSM) to assist the decision-makers in selecting the most feasible AWS. In the study location, Tan Thuan Export and Processing Zone (TTZ) of Ho Chi Minh City, rainwater, industrial effluent and brackish water were selected as AWS options and evaluated for technical, environmental, economic, social and institutional criteria. The stakeholder organisations representing government organisations, industrial-zone management organisations and enterprises were selected as decision-makers based on their willingness to explore AWSs. Four DSM scenarios were derived from the varying decision-making power of the selected stakeholder organisations. The results obtained from applying DSM in TTZ showed rainwater as the most feasible AWS for all the scenarios, while the rank of other AWSs fluctuated for different scenarios. To implement the result of DSM in practice, the government should not only focus on formulating clear technological guidelines on AWS quality but also on providing subsidies and creating an environment of social acceptance of AWSs. The DSM allows the decision-makers to determine the most capable AWS in mitigating freshwater stress issues and the changes required to shift towards these AWSs.